Telegraphy, Typography, and the Alphabet: The Origins of Alphabet Revolutions in the Russo-Ottoman Space. (August 2020) - Kuzuoglu, Ulug
Abstract: This paper explores the history of the alphabet revolutions in the Ottoman Empire and the Russian Empire, beginning in the 1860s and culminating with the new Turkish alphabet and the Soviet latinization movement in the 1920s. Unlike earlier works that have treated these movements separately, this article traces the origins of the alphabet revolutions to the 19th-century communications revolution, when the telegraph and movable metal type challenged the existing modes of knowledge production and imposed new epistemologies of writing on the Muslims in the Russo-Ottoman space. This article examines the media technologies of the era and the cross-imperial debates surrounding various alphabet proposals that predated latinization and suggests that the history of language reform in the Russo-Ottoman world be reevaluated as a product of a modernizing information age that eventually changed the entire linguistic landscape of Eurasia.